P-122 Consistent countywide guidance around anticipatory medications used during the dying phase. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Gibbins, Jane; Scott, Kirsty; Thomas, Michael; Carey, Angela; Ridley, Saul; Newman, Rachel; Thomas, Elizabeth; Hart, Angela; Campbell, Carolyn; Huddart, Melanie; Stevens, Deborah; Smith, Joanne
Abstract : Background: Nationally, there is awareness of the need to improve symptom control for patients at end of life (National VOICES survey). Aim: Dissemination of unified Anticipatory Prescribing Guidance (APG) (incorporating opioid conversion chart, and Hospice 24 hour/7-days-a-week-advice-line-number) to all healthcare settings across Cornwall, backed by a programme of education. Methods: APG developed and rolled out with teaching by specialist palliative care (SPC) teams throughout the county and incorporating attendees' experience to inform the evolution of the project, using Quality Improvement (QI) methodology. Participants were asked to complete a paper questionnaire at the time of teaching to assess changes in knowledge, and an electronic questionnaire 12 weeks after the teaching to capture the impact of such teaching on care of the dying. Quantitative data was analysed using the non-parametric-Wilcoxon-Matched-Pairs. Qualitative data was analysed using thematic analysis until saturation was achieved. Settings: All healthcare sectors; acute and community hospitals, hospices, nursing homes, GPs, district nursing services, secure dementia units and ambulance service. Results: 990 healthcare professionals (HCPs) were taught. There was a statistically significant shift in median knowledge scores (p value<0.001). HCP perceived there was an improvement of symptom control for the dying in clinical practice. Five main themes emerged from the qualitative data; common guidance, improved knowledge and assessment of symptom-control and opioid conversions, advice 24/7-feeling safe, recognising dying and considering what is important to patients, and confidence building. Conclusion: It has been possible to roll out unified APG to a wide range of HCPs to improve their knowledge and confidence. In clinical practice, HCPs perceive it enables improved care to patients in the dying phase by improving symptom control. HCPs described their practice as safer and more efficient. Healthcare professionals formally and informally described the positive impact of having specialist palliative care/hospice-advice-24/7 to back up the guidance on the ground.